Extending the H-Tree Layout Pedigree: An Evaluation - João Miguel Santos; Beatriz Sousa Santos; Paulo Dias; Samuel Silva; Carlos Ferreira (IV'13: Proceedings of the International Conference on Information Visualisation, 2013)
Visualizing large family structures is becoming increasingly important, as more genealogical data becomes available. A space-filling h-tree layout pedigree has been recently proposed to make better use of the available space than traditional representations. In a previous paper we applauded the technique's usage of available space but remarked that it makes generation identification difficult and does not allow navigating to descendants of represented individuals. A set of extensions was proposed to help overcome these limitations and a preliminary evaluation suggested that those extensions enhance the original technique. This paper presents a more thorough evaluation carried out to assess if and how the proposed extensions improve the original h-tree layout pedigree technique. Results suggest that these extensions improve user performance on some tasks, effectively provide new functionality, and generally enhance user experience.